Aplikasi Program Visum untuk Analisis Estimasi Pembebanan Jaringan Jalan di Kota Sungguminasa Kabupaten Gowa - Muhammad Isran Ramli; S. A. Adisasmita; Hajriyanti Yatmar; Syafruddin Rauf; Muralia Hustim; S H Aly; R U Latief; Rosmariani Arifuddin; Suharman Hamzah; M A Abdurrahman (Faculty of Engineering UNHAS, 2024)
The Gowa Regency as a node area that has been designated as one part of the Metropolitan City, an integrated city of Mamminasata, so that Gowa Regency has an important role as a sub-center for the development of Makassar City. The increase in traffic volume has led to transportation problems including queues of vehicles on several roads in the city of Sungguminasa. On several roads in Gowa Regency, there are more potential of congestion occurs because the modes of transportation that pass on these roads have exceeded over the available of road capacity. On the other hand, the distribution modes of transportation is uneven which causes overload capacity on several roads in Gowa Regency, especially Somba Opu District. The purpose of this activity is to analyze the trip assignment of the existing road network conditions and forecast for the next five years based on the existing road level of service values ​​on each road segment according to the origin-destination distribution of trips using the Visum program application. Network assignment by overviewing the performance level of service of existing road network sections shows the classification of service on most road sections with levels A, B and C with indications of stable flow, with the speed is starting to be limited by traffic conditions. In forecasting conditions, it can be seen that the loading of the road network with its performance on most of the sections has decreased in service at levels D and E with indications that traffic is starting to be disrupted and speeds are slowing down. The results of the application of the Visum program in trip assignment for the existing road network with road service level values ​​provide important information as an effort to determine strategies and efforts in mitigation to overcome transportation problems. Detailed level of road service in a road network on several existing road sections will provide an integrated information regarding the potential for diverting several heavy traffic flows in an effort to prevent potential congestion.